Brachyspira hyodysenteriae detection in the large intestine of slaughtered pigs. (January 2018) - Zeeh, Friederike; De Luca, Silvio; Nicholson, Pamela; Grützner, Niels; Nathues, Christina; Perreten, Vincent; Nathues, Heiko
Detection of subclinical Brachyspira hyodysenteriae infection in pig herds using feces is challenging. However, the ability to detect the pathogen in intestinal samples of slaughtered pigs has not been investigated, to our knowledge. Therefore, we determined the detection of B. hyodysenteriae in the colon, cecum, and rectum from slaughtered pigs. We analyzed the correlation between detection rates and intestinal lesions, ingesta or fecal consistency, and time from sample collection until processing. A total of 400 ingesta-mucosal (colon, cecum) and 200 fecal (rectum) samples from 200 pigs originating from 20 different herds were bacteriologically examined using selective culture followed by Brachyspira spp. identification by PCR and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Ingesta or fecal consistency and intestinal lesions were scored. Brachyspira hyodysenteriae was detected in 23 samples from 16 intestines originating from 7 herds. Brachyspira spp. were detected in 96 samples. More intestinal (16) than fecal (7) samples tested positive for B. hyodysenteriae . For Brachyspira spp., this difference was significant (69 vs. 27; p < 0.01). In particular, colon samples tested positive ( n = 42, p = 0.06). Most (91%) of the intestines showed no lesions typical for clinical B. hyodysenteriae infection, and median ingesta or fecal consistency was "soft and formed, " indicating subclinical infection, colonization, or absence of infection. Ingesta from slaughtered pigs, in particular from the colon and sites with lesions, is useful material for detection of B. hyodysenteriae .